2020
DOI: 10.1002/asia.202001102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phenol‐Derived cis‐Vinyl Ethers Using Ethynyl Benziodoxolone

Abstract: The stereoselective synthesis of cis-β-phenoxyvinyl benziodoxolones (cis-β-phenol-VBXs) from an ethynyl benziodoxolone-acetonitrile complex (EBX-MeCN) and various phenols is reported herein. The reaction tolerates different phenol derivatives, including complex natural products, and can be conducted under mild conditions. The synthesis was performed in an aqueous solvent in the absence and presence of a catalytic amount of a base. Selectively mono-and di-deuterated cis-β-phenol-VBXs were also prepared. cis-β-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 96 publications
0
12
0
4
Order By: Relevance
“…C-VBXs can be easily synthesized by coupling vinylboronic acids and suitable hypervalent iodine compounds, [511][512][513][514] whereas several synthetic methods have been reported recently for the synthesis of 'X-VBXs' through the addition reaction of S-, N-, O-, and Xnucleophiles to ethynylbenziodoxoles (EBXs). [515][516][517][518][519][520][521][522][523][524] A common approach for the preparation of X-VBXs starting from EBXs is outlined in Scheme 44.…”
Section: Hypervalent Heterocyclic Compounds Of Iodine(iii)mentioning
confidence: 99%
“…C-VBXs can be easily synthesized by coupling vinylboronic acids and suitable hypervalent iodine compounds, [511][512][513][514] whereas several synthetic methods have been reported recently for the synthesis of 'X-VBXs' through the addition reaction of S-, N-, O-, and Xnucleophiles to ethynylbenziodoxoles (EBXs). [515][516][517][518][519][520][521][522][523][524] A common approach for the preparation of X-VBXs starting from EBXs is outlined in Scheme 44.…”
Section: Hypervalent Heterocyclic Compounds Of Iodine(iii)mentioning
confidence: 99%
“…Importantly, VBXs could be transformed to various vinyl compounds under light‐, photocatalyst‐ or metal‐driven condition. Especially, the addition of phenols to EBXs to construct β ‐aryl ether functionalized VBXs, which were transformed to 2‐iodovinyl phenyl ethers (Figure 1C), have been studied by the groups of Miyake, [18a] Waser, [18b] Yoshikai [18c] and Itoh [18j] . Light mediating fragmentation form VBXs intermediates is an important method to afford 2‐iodovinyl phenyl ethers [18a–c] .…”
Section: Introductionmentioning
confidence: 99%
“…Light mediating fragmentation form VBXs intermediates is an important method to afford 2‐iodovinyl phenyl ethers [18a–c] . Copper catalyzed the breaking of iodobenzene bonds of VBXs to obtain cis ‐iodovinyl ethers [18j] and cis ‐iodoenamide [18k] have been successfully developed by the group of Itoh [18j,k] . In 2021, the group of Jiang reported a new method for synthesis of β ‐iodoenol carbamates with CO 2 via photocatalysis [18l] .…”
Section: Introductionmentioning
confidence: 99%
“…Alkynyl hypervalent iodine compounds containing ethynyl iodonium and cyclic ethynyl benziodoxolone reagents (EBXs) have also been used for the synthesis of various ynamides due to the highly electron-withdrawing nature and leaving group ability of the λ 3 -iodanyl group. However, amino acid-derived ynamide has been synthesized only by using sterically undemanding (β-unsubstituted) or electron-withdrawing group substituted ethynyl hypervalent iodine compounds with limited substrate scope. − , From our previous study on the development of hypervalent iodine compounds, we reported the synthesis of amino acid-derived terminal ynamide by using an unsubstituted EBX-acetonitrile complex under mild reaction conditions (Scheme B) . However, the ynamide could not be formed by using 1-[(triisopropylsilyl)­ethynyl]-1,2-benziodoxol-3­(1 H )-one (TIPS-EBX) whose β-carbon is shielded by a bulky TIPS group (Scheme C).…”
Section: Introductionmentioning
confidence: 99%